Wireless Sensor Data Logging System Design - Noorshafrina Binti Zulkalnain, Noorshafrina (Universiti Teknologi Petronas, 2011)
Wireless Sensor Data Logging System Design is a standalone electronic sensor device that captures and stores data through wireless communication. This system comprises two main integrated components; the Radio Frequency module and the Microcontroller based system. The main goal of this project is to design and construct a data logging system that effectively monitors the device‟s measurement values. In real life applications, most data monitoring system is a passive system. This type of system requires manned guarding on site to manage the devices. Therefore, a standalone data logging system offers a better enhancement system to replace the manned guarding method. The standalone data logger system can be applied by leaving the device alone in any place that requires the measurement of humidity and temperature. These data can be retrieved from EEPROM and transferred to a PC whenever needed by a user. A radio frequency module enables these data travels through wireless transmission medium, whereas the serial communication interface enables communication between the devices and PC. For diverse applications, an alarm system can be implemented if assets and security are the major concerns. The final report presents the development of a data logger system which is an integration of radio frequency module and the microcontroller-based system. The system monitors the device‟s measurement value via a Graphical User Interface. Basically, the system introduces a RF module to replace the hard wired scheme and produce a dynamic data transmission system. It is geared up with a PIC16F877A microcontroller to drive the outputs besides providing communication between devices and a PC. Overall, the project is the best platform to improve the traditional monitoring system and ignites another innovative invention in the future.